Diseño e implementación de un sistema de seguridad de video vigilancia mediante cámaras IP bajo administración SNMP, utilizando una alarma GPRS - Orta Jarrín, Paúl Alexis (2013)
The technology based on the TCP/IP protocol is a widespread technology for establishing communications networks in small or large areas so that the current trend is to digitize any kind of information such as voice, data or video in order to be transmitted in such networks. A strong tendency today is the implementation of IP Surveillance Systems, i.e. networks that allow the transmission of video or voice packets over TCP/IP, using wired or wireless technology which is easy to deploy and maintain, and at the same time it covers large areas.